Building Maintenance Assessment on Official Houses in Stilt Type at Jatiroto Sugar Factory Lumajang District, East Java, Indonesia - Sari, Wahyuni Eka; Sudikno, Antariksa; Santosa, Herry (University of Merdeka Malang, 2021)
The complex of Jatiroto Sugar Factory did not only consist of factory area, but also residential housing. The official house of Jatiroto Sugar Factory was a house destined for the factory officials. On this area of official house, a house was in stilt type. The stilt type in the complex area of Jatiroto Sugar Factory was a unique type, it was differed from the other types of official house. The official house in stilt type has a fascinating specific feature to be examined. However, this official house began to be neglected. A number of houses have been left and not maintained because of the building oldness. The objective of this research was to identify and assess the official house building at Jatiroto Sugar Factory based on the cultural significance value of building maintenance. The descriptive evaluative method was used to assess the building of official house at Jatiroto Sugar Factory. The descriptive method was done and aimed to identify the cultural significance value of building maintenance, while the evaluative method was aimed to determine the maintenance value, so it could result to the value as a direction of building preservation. The result was the value of cultural significance of building maintenance that could be used in the preservation directives.Â DOI:Â https://doi.org/10.26905/lw.v13i1.5108